2019
DOI: 10.1088/1741-2552/ab1673
|View full text |Cite
|
Sign up to set email alerts
|

P300 indicates context-dependent change in speech quality beyond phonological change

Abstract: Objective. Non-invasive physiological methods like electroencephalography (EEG) are increasingly employed to assess human information processing during exposure to multimedia signals. In the quality engineering field, previous research has promoted the utility of the P300 event-related brain potential (ERP) component for indicating variation in quality perception. The present study provides a starting point to test whether the P300 and its two subcomponents, P3a and P3b, are truly reflective of changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The present study puts forward analyses of electrophysiological data gathered in two companion studies (referred to below as study 1 [17] and study 2 [18]), each of which employed a three-stimulus variant of the classic oddball paradigm to examine effects of speech quality degradations on P3. Three-stimulus oddball tasks comprise three stimulus types that vary in presentation rate and task relevance [15]: 'Standards' occur with high frequency (e.g.…”
Section: Present Study: Analysis Of Caep Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study puts forward analyses of electrophysiological data gathered in two companion studies (referred to below as study 1 [17] and study 2 [18]), each of which employed a three-stimulus variant of the classic oddball paradigm to examine effects of speech quality degradations on P3. Three-stimulus oddball tasks comprise three stimulus types that vary in presentation rate and task relevance [15]: 'Standards' occur with high frequency (e.g.…”
Section: Present Study: Analysis Of Caep Componentsmentioning
confidence: 99%
“…In study 1 [17], this underlying perceptual dimensionality of speech quality was varied in the standard and oddball (target, distractor) by applying either signalcorrelated noise ('noisiness'-impaired) or bandpass filtering ('coloration'-impaired) to a spoken word stimulus. In study 2 [18], two types of targets were presented, involving either a single change in quality (T-single) or double changes in quality and spoken word content (T-double). For the content manipulation, two words with different initial phonemes were presented.…”
Section: Present Study: Analysis Of Caep Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurophysiological processing of sound is usually examined using event-related potentials (ERPs). The P3 component has been recently used to evaluate the effects of perceived quality changes in speech ( Uhrig et al, 2019a , b ) and it was reported that the peak amplitude and latency were modulated by sound quality. Likewise, others studies ( Martin et al, 1997 ; Martin and Stapells, 2005 ; Antons et al, 2010 , 2012 ; Porbadnigk et al, 2013 ) also showed that, as the level of degradation decreases when compared to the standard stimulus, which means it is harder for listeners to discriminate the deviant stimulus from the standard stimulus, the amplitude and latency of the P3 component become lower and longer, respectively.…”
Section: Introductionmentioning
confidence: 99%